PGC-1α activator ZLN005 promotes maturation of cardiomyocytes derived from human embryonic stem cells - Liu, Yanping (Aging (Albany NY), 2020)
Human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) have great potential in biomedical applications. However, the immature state of cardiomyocytes obtained using existing protocols limits the application of hPSC-CMs. Unlike adult cardiac myocytes, hPSC-CMs generate ATP through an immature metabolic pathway—aerobic glycolysis, instead of mitochondrial oxidative phosphorylation (OXPHOS). Hence, metabolic switching is critical for functional maturation in hPSC-CMs. Peroxisome proliferator-activated receptor gamma coactivator 1α (PGC-1α) is a key regulator of mitochondrial biogenesis and metabolism, which may help promote cardiac maturation during development. In this study, we investigated the effects of PGC-1α and its activator ZLN005 on the maturation of human embryonic stem cell-derived cardiomyocyte (hESC-CM). hESC-CMs were generated using a chemically defined differentiation protocol and supplemented with either ZLN005 or DMSO (control) on differentiating days 10 to 12. Biological assays were then performed around day 30. ZLN005 treatment upregulated the expressions of PGC-1α and mitochondrial function-related genes in hESC-CMs and induced more mature energy metabolism compared with the control group. In addition, ZLN005 treatment increased cell sarcomere length, improved cell calcium handling, and enhanced intercellular connectivity. These findings support an effective approach to promote hESC-CM maturation, which is critical for the application of hESC-CM in disease modeling, drug screening, and engineering cardiac tissue.